Biofunctionalization of Polymers and their Applications - Nyanhongo, Gibson Stephen; Steiner, Walter; Gübitz, G. M. (Georg M.).; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Chitin, Chitosan and Derivatives for Wound Healing and Tissue Engineering, by Antonio Francesko and Tzanko Tzanov; *Polyhydroxyalkanoates (PHA) and their Applications, by Guo-Qiang Chen; *Enzymatic Polymer Functionalisation: Advances in Laccase and Peroxidase Derived Lignocellulose Functional Polymers, by Gibson S. Nyanhongo, Tukayi Kudanga, Endry Nugroho Prasetyo and Georg M. Guebitz; *Lipases in Polymer Chemistry, by Bahar Yeniad, Hemantkumar Naik and Andreas Heise; *Enzymes for the Biofunctionalization of Poly(Ethylene Terephthalate), by Wolfgang Zimmermann and Susan Billig; *Biology of Human Hair: Know Your Hair to Control It, by Rita Araújo, Margarida Fernandes, Artur Cavaco-Paulo and Andreia Gomes; *Recombinamers: Combining Molecular Complexity with Diverse Bioactivities for Advanced Biomedical and Biotechnological Applications, by José Carlos Rodríguez-Cabello, María Pierna, Alicia Fernández-Colino, Carmen García-Arévalo and Francisco Javier Arias; *Biomimetic Materials for Medical Application Through Enzymatic Modification, by Piergiorgio Gentile, Valeria Chiono, Chiara Tonda-Turo, Susanna Sartori and Gianluca Ciardelli; *Supramolecular Polymers Based on Cyclodextrins for Drug and Gene Carrier Delivery, by Jia Jing Li, Feng Zhao and Jun Li; *Engineering Liposomes and Nanoparticles for Biological Targeting, by Rasmus I. Jølck, Lise N. Feldborg, Simon Andersen, S. Moein Moghimi and Thomas L. Andresen
Chitin, Chitosan and Derivatives for Wound Healing and Tissue Engineering, by Antonio Francesko and Tzanko Tzanov Polyhydroxyalkanoates (PHA) and their Applications, by Guo-Qiang Chen -- Enzymatic Polymer Functionalisation: Advances in Laccase and Peroxidase Derived Lignocellulose Functional Polymers, by Gibson S. Nyanhongo, Tukayi Kudanga, Endry Nugroho Prasetyo and Georg M. Guebitz -- Lipases in Polymer Chemistry, by Bahar Yeniad, Hemantkumar Naik and Andreas Heise -- Enzymes for the Biofunctionalization of Poly(Ethylene Terephthalate), by Wolfgang Zimmermann and Susan Billig -- Biology of Human Hair: Know Your Hair to Control It, by Rita Araújo, Margarida Fernandes, Artur Cavaco-Paulo and Andreia Gomes -- Recombinamers: Combining Molecular Complexity with Diverse Bioactivities for Advanced Biomedical and Biotechnological Applications, by José Carlos Rodríguez-Cabello, María Pierna, Alicia Fernández-Colino, Carmen García-Arévalo and Francisco Javier Arias -- Biomimetic Materials for Medical Application Through Enzymatic Modification, by Piergiorgio Gentile, Valeria Chiono, Chiara Tonda-Turo, Susanna Sartori and Gianluca Ciardelli -- Supramolecular Polymers Based on Cyclodextrins for Drug and Gene Carrier Delivery, by Jia Jing Li, Feng Zhao and Jun Li -- Engineering Liposomes and Nanoparticles for Biological Targeting, by Rasmus I. Jølck, Lise N. Feldborg, Simon Andersen, S. Moein Moghimi and Thomas L. Andresen.
Electronic reproduction.
Keywords: Polymers -- Biotechnology; Polymerization